Cases in educational administration - Reyno, Luz B. 1947-
The aim of the study is to develop cases in educational administration for educational purposes. The case method is an approach in training future educational administrators. It is based on the philosophy that administrative ability can be developed effectively through direct involvement in analyzing and solving problems. Furthermore, the study is an attempt to develop a kind of methodology in writing cases based on the writer's experiences and readings and provide future case writers with criteria and steps in locating cases, excluding and including data, and writing cases.